Evidence in biomass burning smoke for a light-absorbing aerosol with properties intermediate between brown and black carbon. Issue 9 (2nd September 2019) - Adler, Gabriela; Wagner, Nicholas L.; Lamb, Kara D.; Manfred, Katherine M.; Schwarz, Joshua P.; Franchin, Alessandro; Middlebrook, Ann M.; Washenfelder, Rebecca A.; Womack, Caroline C.; Yokelson, Robert J.; Murphy, Daniel M.
Abstract: Biomass combustion produces black carbon (BC) and brown carbon (BrC) aerosols that contribute substantially to warming the Earth's atmosphere. Accurate knowledge of their emissions and absorption per unit mass (mass absorption cross-section; MAC) can be used to quantify the radiative impact of these combustion products. We isolated particles generated from laboratory biomass burning fires by morphology and found that some particles from biomass burning do not correspond to either BC or BrC according to common operational definitions. Unlike BrC, these particles strongly absorb red light, with a MAC and spectral dependence of absorption between that of BrC and BC. They also have intermediate volatility: they survive thermodenuding at 250 °C but do not heat to incandescence in a single particle soot photometer (SP2) instrument. We also found evidence for intermediate properties in ambient wildfire smoke from the 2013 Rim Fire in California. More work is needed to understand how much this intermediate material contributes to atmospheric light absorption from typical combustion, whether or not it corresponds to "tar balls, " and how it may affect previous MAC measurements that were attributed to enhanced absorption by transparent coatings. Copyright © 2019 American Association for Aerosol Research